The Influence of Experience Quality on Domestic Tourists' Behavioral Intentions in Visiting Water Parks - Tumanggor, Grace Fahan Anathasya; Sumar, Sumar (Universitas Muhammadiyah Makassar, 2024)
This work contributes in two ways. First, we want to learn more about the ways that experience quality and image influence value, pleasure, and enjoyment perceptions in the setting of water parks. Our second objective is to comprehend how, in this specific setting, these interactions affect behavioral intentions. Respondents scored each measure on a 5-point Likert scale. The study's conclusions demonstrate how visitor satisfaction and enjoyment are related to one another and how the former positively affects the latter. This lends credence to the theory that visitor happiness has a favorable impact on behavior intentions. While these results are encouraging for attraction considerations in the hospitality and tourism literature, there are still a lot of unexplored research prospects in this field. Researchers should take them into account while evaluating the study's limitations and interpreting the results. First off, there are some limitations in this study's assessment of pre-consumption expectations. Many pre-consumption factors might affect visitors' evaluations and emotions following service consumption. Consequently, it would be fascinating to explore how differences in pre- and post-consumption expectations and assessments impact the visitor experience in research.